Dlstallzatlon of Mandibular Molars Using Mini-Plate Anchorage Fixed on Ramus: Case Report - Tancan Uysal; İbrahim Erhan Gelgör; Zafer Sarı; Doğan Dolanmaz (Galenos Yayinevi, 2006)
Distalization of the lower molars has been one of the most difficult biomechanical problems in the orthodontic treatments. Nowadays it has become possible to move mandibular molars distally with temporary skeletal anchorage systems to correct mandibular crowding and dental asymmetries without lower premolars extraction. In this study, the efficacy and potency of mini-plates in lower molar distalization were evaluated and skeletal, dental and soft tissue changes were analyzed with cephalometric radiographs and dental casts.